Penerapan Framework COBIT Untuk Peningkatan Tata Kelola Teknologi Informasi - Kuryanti , Sandra Jamu; Adiwihardja , Cep; Suryadi , Ade; Ambarsari , Diah Ayu (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2023)
IT governance is used to monitor and control decisions regarding current IT performance, to improve IT performance in the future. To improve PT. ASAHIMAS FLAT GLASS TBK Jakarta in improving its IT governance using COBIT 5.0, currently the domain used is MEA (Monitor, Evaluate, and Assess), which consists of MEA01 ((Monitoring, Evaluate and Assess Performance and Confirmance ), MEA02 (Monitor, Evaluate and Asses Compliance with External Requirements), and MEA03 (Monitor, Evaluate and Assess Compliance with External Requirements). After conducting research using COBIT 5.0, the results were obtained in the form of GAP, GAP was 1.32 in ME01, GAP was 1.3 in ME02, and a GAP of 1.3 in ME03. With this GAP, agencies need to make improvements to several processes, especially in the MEA domain. This research was created with the aim of improving governance at PT. ASAHIMAS FLAT GLASS TBK Jakarta.